Challenges and Implementation of Drug Inventory Control in Hospitals: Literature Review - Putri Nadya Syahidah; Ayun Sriatmi; Septo Pawelas Arso (Green Publisher Indonesia, 2024)
One of the most important hospital management functions is the management of pharmaceutical drug logistics. Drug planning is the process of selecting the type and quantity of drugs required for procurement. Various managerial theories can be used to analyze drug control in pharmaceutical installations, and three research journals on pharmaceutical drug logistics control in hospitals are used for this literature review. The results of the analysis show that there are four methods in drug control: EOQ (economic purchase amount), ABC (better control at all times), ROP (point of repurchase), and VEN (vital, essential, and non-essential). One way to help pharmaceutical logistics stock inventory be more efficient, efficient, and responsive to patient needs and service dynamics is to apply one or a combination of these four methods. Good drug stock management can ensure optimal inventory control, improve service quality, reduce costs, and better manage risks.